Minimally invasive left ventricular assist device implantation: at the crossroads - Patil, Nikhil Prakash; Popov, Aron F.; Simon, André R. (Journal of Thoracic Disease; Vol 7, No 4 (April 28, 2015): Journal of Thoracic Disease, 2015)
Continuous-flow left ventricular assist devices (CF-LVADs) are now established therapy for end stage heart failure, as not only bridge to transplant/recovery/decision but also as destination therapy. What remains somewhat divisively opinionated, however, is the optimal approach—is full sternotomy still the “standard of care” or are minimally invasive techniques making “smaller, yet safer” the new norm for LVAD implantation in appropriate patients? In this article (1), Maltais and colleagues review their single-center experience with minimally invasive CF-LVAD implantation.